The Effectiveness of the Business Capital Assistance Program in Improving the Performance of MSMEs : JEL Classification: G28, H84, L26, O12, R11 - Nurul Amelia Malik; Fahrul Kahfi; Fey Armita (Generasi Sains Indonesia, 2026)
This study reviews the effectiveness of the Business Capital Assistance Program to improve the performance of the micro, small and medium scale businesses in the city of Palu in the context of economic recovery from disaster in Indonesia. The study will assess whether government support for enterprises in the form of financial assistance has a significant impact on enterprise income growth, enterprise production and sales performance, and enterprise continuity. The quantitative explanatory approach was used and the type of design was cross sectional. The data were gathered by using structured questionnaires and the respondents were the owners of MSMEs who received business capital assistance from the local government. The data was analyzed descriptively and multiple regression analysis was used to determine the relationship between capital assistance and MSME performance. The results indicate that business capital assistance is positively and significantly influencing the performance of the MSMEs. Financial assistance to the beneficiary enterprises led to increased income, growth of production and sales activity, and better stability of operations in the enterprise. The study also finds that the effectiveness of a programme is influenced by the characteristics of the sector: it is more effective for trade and food-related enterprises. This study's novelty is in its resilience-based assessment of a localized government assistance program in a post-disaster urban economy. Results offer theoretical and practice implications for developing more adaptive and sustainable MSME development policies in vulnerable areas.